Marital History and Survival After Stroke - Matthew E. Dupre; Renato D. Lopes (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Stroke is among the leading causes of disability and death in the United States, and nearly 7 million adults are currently alive after experiencing a stroke. Although the risks associated with having a stroke are well established, we know surprisingly little about how marital status influences survival in adults with this condition. This study is the first prospective investigation of how marital history is related to survival after stroke in the United States. Methods and Results Data from a nationally representative sample of older adults who experienced a stroke (n=2351) were used to examine whether and to what extent current marital status and past marital losses were associated with risks of dying after the onset of disease. Results showed that the risks of dying following a stroke were significantly higher among the never married (hazard ratio [HR], 1.71; 95% CI, 1.31–2.24), remarried (HR, 1.23; 95% CI, 1.06–1.44), divorced (HR, 1.23; 95% CI, 1.01–1.49), and widowed (HR, 1.25; 95% CI, 1.10–1.43) relative to those who remained continuously married. We also found that having multiple marital losses was especially detrimental to survival—regardless of current marital status and accounting for multiple socioeconomic, psychosocial, behavioral, and physiological risk factors. Conclusions Marital history is significantly associated with survival after stroke. Additional studies are needed to further examine the mechanisms contributing to the associations and to better understand how this information can be used to personalize care and aggressively treat vulnerable segments of the population.